Linguistic discourse in the system of language manipulative technologies (based on the material of english political advertising) - Aliyeva, Gulchohra Babali; Borymska, Oksana; Kyshenia, Yuliia; Kovalchuk, Oksana; Zoya, Mytiay (Amazonia Investiga, 2023)
This paper attempts to explain what manipulation means and how it differs from other linguistic and manipulative technologies. The article deals with a number of issues related to the definition of manipulation since both in modern language and in specialized literature the concept of manipulation is used in many meanings. The purpose of the article is to eliminate the ambiguity surrounding the concept of language manipulation. We put forward the hypothesis that manipulation is an illegitimate linguistic process justified by the structure of human consciousness and the mechanisms of social life. The discourse analysis, descriptive and contextual methods made possible the linguistic analysis of fragments of political speeches of famous American politicians. As a result, the linguistic markers for deciphering the manipulative discourse strategy are identified, and the discourse structure of a political manipulative speech is described. The main types of strategies for exercising manipulative influence are considered on the examples of fragments of political speeches and slogans of American politicians Hillary Clinton, Donald Trump, and Barack Obama. The author reveals the physical and cultural concepts of manipulation and analyzes the linguistic forms that can underlie the manipulation of words.